Effect of Modified Septic Tank on Groundwater Quality around Federal University of Agriculture, Abeokuta, South-west Nigeria - Olatunde, Kofoworola; Sarumi, Modupe; Abdulsalaam, Sadiq; Bada, Babatunde; Oyebanji, Funmilola (Applied Environmental Research, 2020)
Groundwater forms a very important part of the water supply chain and its quality can be affected by improperly constructed septic tanks used by homeowners in peri-urban locations such as Abeokuta in recent times. Sixty groundwater samples collected from hand-dug wells ≤15m from septic tanks were analysed for physicochemical and bacteriological parameters using standard procedures. Results were integrated with multivariate and hydrogeochemical analyses to assess the effect improperly built septic tanks have on groundwater quality around the Federal University of Agriculture, Abeokuta. The range of values for the measured parameters include: pH (6.26 – 8.66), EC (83 – 1035 μS cm-1), TDS (42 – 621 mg L-1), Mg2+ (2 – 60 mg L-1), NO3- (5.09 – 17 mg L-1), Fe (-.04 – 5.32 mg L-1), BOD (0.1 – 13.2) and E. Coli (ND – 41×10 cfu mL-1). The abundance of major ions are in the order Ca2+˃Mg2+˃K+˃ Na+ and Cl- ˃SO42- >HCO3- >NO3- ˃PO42-. The piper trilinear plot shows that the dominant hydrochemical facies in the study area is the Ca2+– Cl- type. A correlation analysis and a principal component analysis both reflect intrusions from biological wastes such as surrounding septic tanks or municipal waste disposals as well as dissolutions from basal rocks. The possibility of infiltration from sewage into groundwater is confirmed by the number of samples with high BOD, NO3-, and E. coli concentrations. Contamination of groundwater with sewage exposes the populace to acute excreta-related illness. This therefore calls for stringent monitoring and management measures to be put in place by relevant regulatory authorities to safeguard the human health and environment within the study area.